2021
DOI: 10.1101/2021.02.03.429564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RAD51 nuclear recruitment and inhibition towards innovative strategies against pancreatic cancer

Abstract: RAD51, a key player in the homologous recombination (HR) mechanism, is a critical protein to preserve genomic stability. BRCA2, upon DNA damage, promotes RAD51 fibrils disassembly and its nuclear recruitment. Here, we use BRC4, a peptide derived from the fourth BRC repeat of BRCA2; BRC4 induces RAD51 defibrillation through a 'domino' effect, eroding fibrils from their termini, and yielding monomeric RAD51. The congruence among several techniques (static and dynamic light scattering, negative staining transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nevertheless, we do consider that the remaining RAD51 terminals can be responsible for the templating effect in ptDCC. This consideration is supported by our recent investigations, reporting that the disassembly of RAD51 fibrils is mediated by BRC4 as a gradual, monomer-by-monomer depolymerization process, starting from the available terminus of the fibril. This model gives space for the interaction of small molecules with the available terminals of RAD51 fibrils, where they can eventually lock the fibril and prevent BRC4 interaction, thoroughly inhibiting fibrils disassembly and, consequently, RAD51 activity.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, we do consider that the remaining RAD51 terminals can be responsible for the templating effect in ptDCC. This consideration is supported by our recent investigations, reporting that the disassembly of RAD51 fibrils is mediated by BRC4 as a gradual, monomer-by-monomer depolymerization process, starting from the available terminus of the fibril. This model gives space for the interaction of small molecules with the available terminals of RAD51 fibrils, where they can eventually lock the fibril and prevent BRC4 interaction, thoroughly inhibiting fibrils disassembly and, consequently, RAD51 activity.…”
mentioning
confidence: 97%
“…Interestingly, the two 19 F NMR signals of 7 returned sharp to their original shape upon addition of BRC4 (Figure 4, blue), suggesting a competition between 7 and BRC4 for the same protein binding site. Given the higher affinity of BRC4 for RAD51 (nM range) 27 compared to 7, the compound was completely displaced by BRC4, thus no binding of 7 were visible in the presence of BRC4 (data not shown). These data suggested that 7 binds in the same pocket occupied by BRC4, already structurally characterized by Pellegrini et al 22 To predict the binding mode of 7 to RAD51, we performed docking simulations in the area where BRC4 binds RAD51 (named site I and site II).…”
mentioning
confidence: 99%